(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Pregnant women have been widely recognized as avulnerable group from health point of view. They need more food than normalperson for the proper nourishment of the growing fetus. A total of hundredpregnant women who were in their third trimester were selected for the study.Indian women have very high prevalence of anemia as well as malnutrition in theworld. Hemoglobin (Hb) level in their blood is reported below the normal valuei. e 11-14gm According to National Family health survey of India -3,prevalenceof anemia among women of 15-49 years age group is found to be 55.3 %, in pregnantwomen it was 58% and in children less than three years of age it was 80 %. Itis underlying cause for 20 -40 % maternal death, thus anemia is the mostfrequently observed nutritional diseases in the world. In India, anemia is thesecond most common cause of maternal death, accounting for 20% total maternaldeaths. The food intake consisted of rice, nuts and pulses andvegetables, meaning that it was mainly plant-based food. Rice behaved as astrongly inferior good in economic terms, meaning that its consumptionincreased in spite of its price increase. Especially, rural, poor women withaccess to rice fields increased their rice intake and decreased their intake ofnon-rice staple foods. Reasons for the continued rice intake included that thewomen had been accustomed to eating rice since they were born and that cookingmethods for non-rice staple foods were difficult. The intake of nuts and pulsesand vegetables increased for most groups. Nuts and pulses were an importantsupplier of calcium and iron, and vegetables were an important supplier ofvitamin A. Urban poor and rural poor, landless women experienced a decreasedintake of most nutrients in the transition period but an increased intake.